Climate-smart and resilient rice production practices in the MFS - Ahmed, S.; Miajy, Abdullah; Khatun, Amina; Bhandari, Humnath (International Rice Research Institute, 2023)
The rising concerns of over-exploitation of groundwater resources, increasing cost of inputs and cultivation, timely availability of labor and energy, degradation of soil health, and climate change prevail in major agri-food systems in Bangladesh. Thus, reversing the unsustainable way of practicing agriculture to climate-smart agriculture would be key to sustainable agricultural development and productivity. Climate Smart is an approach to agricultural production, that is concerned with the management of available resources, with the latest agricultural management practices and machinery, especially under a particular set of socio-economic and environmental conditions. It works to improve food security and sustainable development goals (SDGs). Therefore, if climate-smart agriculture is implemented at the right time, with the necessary resources, techniques, and knowledge in a particular area, it can lead to food security along with enhancing adaptive capacity and reducing GHG potential for sustainable agricultural production. In Bangladesh, the SI-MFS initiative has been working with some climate-smart agricultural production systems e.g., direct-seeded rice (DSR), sorjan systems crop production, and nano-fertilizer applications.